2007
DOI: 10.1177/0959683607082551
|View full text |Cite
|
Sign up to set email alerts
|

Environmental change and settlement shifts in Upper Egypt during the Predynastic: charcoal analysis at Adaïma

Abstract: What was the environmental setting for changes in the settlement pattern of Adaïma, a mid-fourth to early-third millennium site in the Egyptian Nile valley? Analysis of charcoal collected from the archaeological soil was performed on contexts from several periods. The settlement was set up in an environment where the vegetation was probably more extended, with more wooded desert margins. Over 600 years, changes in the charcoal spectrum reflect a possible local desertification and the impact of human activities… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 8 publications
0
13
0
1
Order By: Relevance
“…Floss (silky hair, akund floss, 2-3 cm long, 12-42 microns wide) from seed stands have been used as stuffing for pillows and mattresses. This use was known in the Acient Egypt and by 1910, Calotropis procera was cultivated in Djibouti, producing about 1200 kg seed hair per hectare [31,33]. Even recently, seed hair from Calotropis has been presented as a potential silk replacer [50].…”
Section: Use As a Building Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…Floss (silky hair, akund floss, 2-3 cm long, 12-42 microns wide) from seed stands have been used as stuffing for pillows and mattresses. This use was known in the Acient Egypt and by 1910, Calotropis procera was cultivated in Djibouti, producing about 1200 kg seed hair per hectare [31,33]. Even recently, seed hair from Calotropis has been presented as a potential silk replacer [50].…”
Section: Use As a Building Materialsmentioning
confidence: 99%
“…Bast fibres of C. gigantea have been noted to have increased crystallinity upon treatment with 5w% alkali solution, leading to higher tensile strength of the material [66]. During World War 1, rubber for tyres was produced from the C. procera's latex [33]. Although, the composition of the latex of the plant is very complex, it can consist of up to 25-35% of natural rubber [poly(cis-1,4-isoprene, 1), Fig.…”
Section: Use As a Building Materialsmentioning
confidence: 99%
“…Une fois le phasage des nécropoles posé à partir d'un ordonnancement séquentiel des tombes -celui-ci conduisant, au passage, à reconsidérer la chronologie traditionnelle -, une approche topo-chronologique raisonnée de l'habitat a pu être engagée sur la base de cette classifi cation et des comparaisons avec les mobiliers funéraires. De cette analyse et du croisement de ses résultats avec les travaux des environnementalist es et des anthropologues, sur la paléo-démographie notamment, il est fi nalement résulté une image d'abandon progressif de l'habitat traduisant une diminution de la population (Newton, Midant-Reynes, 2007 ;Crubezy et al, 2008) Une approche fi ne en aire ouverte n'était pas envisageable ; il importait, en eff et, de mettre en place une fouille à diff érentes vitesses sur la base d'un enregist rement st ratigraphique rigoureux comme cela est régulièrement pratiqué en archéologie urbaine métropolitaine. Il s'agissait aussi de procéder à la fouille -et à l'étude in situ étant donné l'état de préservation des squelettesde la centaine de sépultures mises au jour durant chaque campagne.…”
Section: Archéopages Hors Série Octobre 2010unclassified
“…However, during continuous treadmill testing, Breithaupt et al (2012) found that many obese adolescents are unable to meet at least two of the maximality criteria: peak of oxygen consumption (VO2peak), heart rate > 90% of the theorical maximal value, a respiratory quotient above 1.05 and a feeling of maximal exertion. Moreover, the rating of perceived exertion (RPE) reported by obese adolescents at the end of graded tests corresponds to moderate-vigorous rather than maximal intensities, whether in the laboratory (Marinov et al, 2002;Lazaar et al, 2006) or the field (Rey et al, 2016;Thivel et al, 2017). This finding confirms their difficulty in reaching a state of total exhaustion during a maximal test.…”
Section: Introductionmentioning
confidence: 99%